2016
DOI: 10.1007/s10479-016-2193-5
|View full text |Cite
|
Sign up to set email alerts
|

A computational approach to steady-state convergence of fluid limits for Coxian queuing networks with abandonment

Abstract: Many-server queuing networks with general service and abandonment times have proven to be a realistic model for scenarios such as call centers and health-care systems. The presence of abandonment makes analytical treatment difficult for general topologies. Hence, such networks are usually studied by means of fluid limits. The current state of the art, however, suffers from two drawbacks. First, convergence to a fluid limit has been established only for the transient, but not for the steady state regime. Second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…Queuing theory has been studied rigorously over the last century [92,88,193]. However, queue abandonment is one aspect of human behavior that is poorly understood in queuing theory [174,214]. Prior literature has explored the reasons behind abandonment and showed that it's highly affected by long wait times [134].…”
Section: Queue Abandonmentmentioning
confidence: 99%
“…Queuing theory has been studied rigorously over the last century [92,88,193]. However, queue abandonment is one aspect of human behavior that is poorly understood in queuing theory [174,214]. Prior literature has explored the reasons behind abandonment and showed that it's highly affected by long wait times [134].…”
Section: Queue Abandonmentmentioning
confidence: 99%